Climate Change Impacts on Water Resources Management : Adaptation Challenges and Opportunities in Northeast Brazil - World Bank (Washington, DC, 2014)
The Latin America and Caribbean (LAC) region has a unique mix of qualities and challenges when it comes to the environment. It is exceptionally endowed with natural assets, with globally significant biodiversity and valuable crops, and also harbors the world's greatest carbon sink in the Amazon. Over the past twenty years, the LAC region has made impressive gains in tackling these issues. It leads the developing world in biodiversity conservation and natural resource management and is at the forefront in reducing urban pollution. The environment and water resources occasional paper series is a publication of the Environment and Water Resources Unit (LCSEN) of the sustainable development department in the World Bank's Latin America and the Caribbean Region. The purpose of the series is to contribute to the global knowledge exchange on innovation in environmental and water resources management and the pursuit of greener and more inclusive growth. The papers seek to bring to a broader public-decision makers, development practitioners, academics and other partners-lessons learned from World Bank financed projects, technical assistance and other knowledge activities jointly undertaken with partners. This project proved to be a critical first step in better understanding how climate change will translate to water scarcity, and how the drought-prone and rapidly developing Northeast Region of Brazil could adapt through more flexible water management and allocation strategies.